1993
DOI: 10.2134/jeq1993.00472425002200020009x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amount and Method of Irrigation Water Application on Leaching of Atrazine

Abstract: A study was conducted to relate leaching of a herbicide, atrazine [6‐chloro‐N‐ethyl‐N′‐(1‐methylethyl)‐1,3,5‐triazine‐2,4,‐diamine], and inorganic water tracers, Br− and Cl−, to the amount of deep‐percolating water produced from irrigation. Soil at the site was classified as a Dehli Loamy Sand (Mixed, Thermic, Tepic Xeropsamment) which was an unstructured sandy soil that was low in organic C content, conditions conducive to solute leaching. The relationship between depth of solute movement and amount of deep‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 5 publications
3
25
0
Order By: Relevance
“…Flood irrigation scenarios yielded higher predicted simazine detection frequencies and ground water concentrations than sprinkler scenarios (Table IV). Irrigation efficiency and frequency both influence rates of leaching (Miller et al, 1965;Oster et al, 1972;Troiano et al, 1993), so both effects are responsible for the differences observed here. An effect of crop type is also evident, potentially attributable to both application timing (early Note Detection frequency based on analytical reporting limit of 0.05 ug L −1 .…”
Section: Mass Budgetsmentioning
confidence: 65%
See 3 more Smart Citations
“…Flood irrigation scenarios yielded higher predicted simazine detection frequencies and ground water concentrations than sprinkler scenarios (Table IV). Irrigation efficiency and frequency both influence rates of leaching (Miller et al, 1965;Oster et al, 1972;Troiano et al, 1993), so both effects are responsible for the differences observed here. An effect of crop type is also evident, potentially attributable to both application timing (early Note Detection frequency based on analytical reporting limit of 0.05 ug L −1 .…”
Section: Mass Budgetsmentioning
confidence: 65%
“…Soil data for the coarse Fresno County Delhi loamy sand used as the representative root zone soil profile are reported elsewhere (Troiano et al, 1993). Summarizing, sand content varied from 84 to 91 percent through the profile, with soil mass fraction organic carbon (OC) steadily decreasing from 0.0071 in the 0-15 cm depth to <0.0001 at the bottom of the profile.…”
Section: Root Zone Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, pesticides and other chemicals are incorporated in the irrigation; the leaching of pesticides and their breakdown products increases in direct relation with an increase in the amount of percolating water produced by irrigation (Asare et al, 2001). The close association between leaching and amount of deep-percolating water produced by irrigation is expected because leaching occurs through dissolution of solute in soil solution and subsequent movement with soil water (Troiano et al, 1993). Pesticides in California ground water have been found in a variety of diverse climatic and soil conditions, including semiarid, intensively-irrigated, and coarse soil areas with shallow depth to ground-water (Spurlock, 2000).…”
Section: Introductionmentioning
confidence: 99%